KAJIAN SEMIOTIKA: REPRESENTASI IDENTITAS KOSMOPOLITAN PADA KONTEN VISUAL FOTOGRAFI DI INSTAGRAM @ANOMALI.BALI - Tjahjadi, Clarence Venedictta; Dektisa, Andrian; Wahyudi, Anang Tri (Narada : Jurnal Desain dan Seni, 2025)
Cosmopolitan identity is a modern and open-minded concept along with the evolution of the globalization era. The concept of cosmopolitanism can be applied in various aspects, one of which is in photography as visual content. This study discusses the cosmopolitan identity represented through photography as visual content on Anomali Coffee Bali’s  Instagram. Semiotics concepts such as denotation, connotation, and myth are used to understand the signs in the photos. Using qualitative research method to analyze how cosmopolitan identity reflects through visual elements in photography content. This study uses data from literature studies that underpins the theory of research as well as visual data from @anomali.bali on Instagram. This research was conducted to provide an understanding of how a cafe, namely Anomali Coffee in Bali represents a cosmopolitan identity to the audience through their photography content.